Extracellular vesicles: immunomodulation, diagnosis, and promising therapeutic roles for rheumatoid arthritis - Desalegn Abebaw; Yibeltal Akelew; Yibeltal Akelew; Adane Adugna; Zigale Hibstu Teffera; Bantayehu Addis Tegegne; Abebe Fenta; Bantegize Selabat; Gashaw Azanaw Amare; Mamaru Getinet; Mohammed Jemal; Temesgen Baylie; et al. (Frontiers in Immunology, 2024)
Extracellular vesicles (EV) can be produced as part of pathology and physiology with increased amounts in pathological conditions. EVs can carry and transfer cargo such as proteins, nucleic acids, and lipids to target cells and mediate intercellular communication resulting in modulation of gene expression, signaling pathways, and phenotype of recipient cells. EVs greatly influence the extracellular environment and the immune response. Their immunomodulatory properties are crucial in rheumatoid arthritis (RA), a condition marked by dysregulated immune response. EVs can modulate the functions of innate and adaptive immune cells in RA pathogenesis. Differentially expressed EV-associated molecules in RA, such as microRNAs (miRNAs), long-noncoding RNAs (lncRNAs), messenger RNAs (mRNAs) and proteins are promising markers to diagnose the disease. miRNA, lncRNA, and circular RNA (circRNA) cargos in EV regulate inflammation and the pathogenic functions of RA fibroblast-like synoviocytes (RA-FLS). Downregulated molecules in RA tissue and drugs can be encapsulated in EVs for RA therapy. This review provides an updated overview of EVs’ immunomodulatory, diagnostic, and therapeutic roles, particularly emphasizing mesenchymal stem cell-derived EVs (MSC-EVs).